EFFECT OF AEROBIC EXERCISE AND RESISTED EXERCISE AMONG POST- OPERATIVE BREAST CANCER WOMENS - SHANMUGANANTH, E.; SRIDHAR, ANANYA; REKHA.K, (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer is a common condition worldwide. It requires an intense and prolonged treatment. No woman is truly at low risk of developing a breast cancer. Breast cancer is a malignant tumor where the group of cancer cells grow into (invade) the surrounding tissues and spread (metastasize) to distant areas of the body. India’s incidence is 100,000 women per year and death rate is 90,659 (as per 2010). Physical exercise has been defined as a good intervention to overcome the compromised quality of life and aerobic capacity. Recent evidence also suggests that it decreases the chances of morbidity and mortality. The objective was to determine the effect of Aerobic Exercise and Resisted Exercise on Exercise tolerance and QOL among breast cancer females. A Quasi Experimental Study was done in our Cardio- Pulmonary OPD, the outcome measures being Six Minute Walk Distance, Quality Of Life.11 subjects with breast cancer who are receiving chemotherapy, radiotherapy and hormone therapy aged between 40 to 65 years were recruited. All the subjects were clinically assessed for Exercise Tolerance and QOL. Subjects who fulfill the selection criteria receive Aerobic Exercises and Resisted Exercises for 4times a week for 6 weeks. Changes in all the outcomes noted. Improvement is seen more in QOL and Exercise Tolerance with Aerobic and Resisted exercise p 0.00. The study concludes that aerobic exercise and resisted exercise is effectiveand it has been proved that Aerobic Exercise and Resisted exercise improves QOL and Exercise Tolerance and thereby aerobic exercise and resisted exercise can be recommended in treating Breast cancer females.